New approach to ideal inductors stored energy nature - Ayoub, H. Y.; Milanez, D. L.; de Souza, C. R.; Ruppert, E. (IEEE Computer Soc, 1999)
Nonlinear load compensation required the definition of new concepts of electric power. With basis on these new concepts the nature of the stored energy stored in ideal inductors is theoreticaly characterized in this work. Computer simulation and theory agree when applied to an isolated alternator.